Obituary : Ruby Whitelaw - Neil McMillan (Scottish Journal of Residential Child Care)
It is with deep respect and gratitude that we remember Doctor Ruby Whitelaw, a dedicated and compassionate advocate for residential childcare, whose contributions to the field have left a lasting impact. Ruby passed away suddenly on 20th December 2024 and will be dearly missed by colleagues, friends, and all those whose lives she touched.